Tumour subregion analysis of colorectal liver metastases using semi-automated clustering based on DCE-MRI: Comparison with histological subregions and impact on pharmacokinetic parameter analysis. Issue 126 (May 2020) - Franklin, James M.; Irving, Benjamin; Papiez, Bartlomiej W.; Kallehauge, Jesper F.; Wang, Lai Mun; Goldin, Robert D.; Harris, Adrian L.; Anderson, Ewan M.; Schnabel, Julia A.; Chappell, Michael A.; Brady, Michael; Sharma, Ricky A.; et al.
Highlights: Liver metastases can be divided into subregions using DCE-MRI. Tumour subregions show a good concordance with the specimen after resection. Subregions show significance differences in parameters derived from DCE-MRI. Tumour subregion analysis may improve our understanding of tumour biology. Abstract: Purpose: To use a novel segmentation methodology based on dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) to define tumour subregions of liver metastases from colorectal cancer (CRC), to compare these with histology, and to use these to compare extracted pharmacokinetic (PK) parameters between tumour subregions. Materials and Methods: This ethically-approved prospective study recruited patients with CRC and ≥1 hepatic metastases scheduled for hepatic resection. Patients underwent DCE-MRI pre-metastasectomy. Histological sections of resection specimens were spatially matched to DCE-MRI acquisitions and used to define histological subregions of viable and non-viable tumour. A semi-automated voxel-wise image segmentation algorithm based on the DCE-MRI contrast-uptake curves was used to define imaging subregions of viable and non-viable tumour. Overlap of histologically-defined and imaging subregions was compared using the Dice similarity coefficient (DSC). DCE-MRI PK parameters were compared for the whole tumour and histology-defined and imaging-derived subregions. Results: Fourteen patients were included in the analysis. Direct histological comparison with imaging was possible in nine patients. Mean DSC for viable tumour subregions defined by imaging and histology was 0.738 (range 0.540-0.930). There were significant differences between K trans and kep for viable and non-viable subregions (p < 0.001) and between whole lesions and viable subregions (p < 0.001). Conclusion: We demonstrate good concordance of viable tumour segmentation based on pre-operative DCE-MRI with a post-operative histological gold-standard. This can be used to extract viable tumour-specific values from quantitative image analysis, and could improve treatment response assessment in clinical practice.